THE AN INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUE COMBINATION WITH ULTRASOUND MORE EFFECTIVE IN REDUCE PAIN COMPARED TO A COMBINATION OF STRAIN COUNTERSTRAIN WITH ULTRASOUND IN PIRIFORMIS SYNDROME PATIENTS - Baktiyasa, I Nyoman; Wibawa, Ari; Griadhi, I Putu Adiartha (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Piriformis Syndrome is a collection of symptoms such as pain, tingling or numbness from the buttocks down to the foot. In this condition, patients can be given intervention with Integrated Neuromuscular Inhibition Technique, Strain Counterstrain and Ultrasound. With Paired Sample t-test on Group 1 that got the value of p =0.000 with mean differences 2.940±0.96,while at Group 2 that got the value of p=0.000 with mean differences 1.910±0.60. In test of difference between Group 1 and Group 2 using Independent Sample t-test showed p=0,010 (p<0,05). These research showed that combination of Integrated Neuromuscular Inhibition Technique with Ultrasound is more effective in relieving pain than combination of Counterstrain Strain with Ultrasound in Piriformis Syndrome. Keyword: Integrated Neuromuscular Inhibition Technique, Strain Counterstrain, Ultrasound, Piriformis Syndrome